The interplay between herbal medicines and gut microbiota in metabolic diseases - Wang, Lijie; Gou, Xiaoling; Ding, Yin; Liu, Jingye; Wang, Yue; Wang, Yaqian; Zhang, Jing; Du, Leilei; Peng, Wei; Fan, Gang (Frontiers in Pharmacology, 2023)
Globally, metabolic diseases are becoming a major public health problem. Herbal medicines are medicinal materials or preparations derived from plants and are widely used in the treatment of metabolic diseases due to their good curative effects and minimal side effects. Recent studies have shown that gut microbiota plays an important role in the herbal treatment of metabolic diseases. However, the mechanisms involved are still not fully understood. This review provides a timely and comprehensive summary of the interactions between herbal medicines and gut microbiota in metabolic diseases. Mechanisms by which herbal medicines treat metabolic diseases include their effects on the gut microbial composition, the intestinal barrier, inflammation, and microbial metabolites (e.g., short-chain fatty acids and bile acids). Herbal medicines can increase the abundance of beneficial bacteria (e.g., Akkermansia and Blautia), reduce the abundance of harmful bacteria (e.g., Escherichia–Shigella), protect the intestinal barrier, and alleviate inflammation. In turn, gut microbes can metabolize herbal compounds and thereby increase their bioavailability and bioactivity, in addition to reducing their toxicity. These findings suggest that the therapeutic effects of herbal medicines on metabolic diseases are closely related to their interactions with the gut microbiota. In addition, some methods, and techniques for studying the bidirectional interaction between herbal medicines and gut microbiota are proposed and discussed. The information presented in this review will help with a better understanding of the therapeutic mechanisms of herbal medicines and the key role of gut microbiota.